2019
DOI: 10.1016/j.ajhg.2019.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Recessive Truncating Mutations in ALKBH8 Cause Intellectual Disability and Severe Impairment of Wobble Uridine Modification

Abstract: The wobble hypothesis was proposed to explain the presence of fewer tRNAs than possible codons. The wobble nucleoside position in the anticodon stem-loop undergoes a number of modifications that help maintain the efficiency and fidelity of translation. AlkB homolog 8 (ALKBH8) is an atypical member of the highly conserved AlkB family of dioxygenases and is involved in the formation of mcm5s2U, (S)-mchm5U, (R)-mchm5U, mcm5U, and mcm5Um at the anticodon wobble uridines of specific tRNAs. In two multiplex consangu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 44 publications
2
46
0
Order By: Relevance
“…Neither had seizures, in contrast to the majority of subjects previously reported. Six out of seven affected individuals from both unrelated Saudi kindreds reported by Monies et al (2019) had a diagnosis of epilepsy with the latest age of onset being 2 years of age. Both affected siblings described herein display structural brain anomalies including mild to moderate cerebral volume loss, mild to moderate cerebellar vermian hypoplasia, variable degrees of thinning of the corpus callosum, and abnormal myelination for age on brain MRI, whereas abnormalities on brain MRI in the form of nonspecific arachnoid granulation were observed in only one out of the three affected individuals with brain imaging in Monies et al (2019).…”
Section: Discussionmentioning
confidence: 96%
“…Neither had seizures, in contrast to the majority of subjects previously reported. Six out of seven affected individuals from both unrelated Saudi kindreds reported by Monies et al (2019) had a diagnosis of epilepsy with the latest age of onset being 2 years of age. Both affected siblings described herein display structural brain anomalies including mild to moderate cerebral volume loss, mild to moderate cerebellar vermian hypoplasia, variable degrees of thinning of the corpus callosum, and abnormal myelination for age on brain MRI, whereas abnormalities on brain MRI in the form of nonspecific arachnoid granulation were observed in only one out of the three affected individuals with brain imaging in Monies et al (2019).…”
Section: Discussionmentioning
confidence: 96%
“…For example, mouse KO of the tRNA modification enzyme Alkbh8 caused mismodification of several distinct tRNA isoacceptors at the critical wobble uridine position, but gave no overt phenotype 29 , 30 . However, later studies showed defects in selenoprotein synthesis and stress tolerance in the Alkbh8 KO mice 31 , 32 , and it was recently reported that homozygous inactivating mutations in the human ALKBH8 gene causes intellectual disability and general developmental delay 33 . Likewise, more detailed studies, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, defects in tRNA modification have emerged as the cause of diverse neurological and neurodevelopmental disorders, thereby highlighting the critical role of tRNA modification in human health and physiology (Angelova et al, 2018; Ramos & Fu, 2019). In particular, the brain appears to be sensitive to any perturbation in translation efficiency and fidelity brought about by defects in tRNA modifications, as evidenced from the numerous cognitive disorders linked to tRNA modification enzymes such as: the Elongator complex (Hawer et al, 2018; Kojic & Wainwright, 2016); ADAT3 (Alazami et al, 2013; El‐Hattab et al, 2016; Ramos, Han, et al, 2019); NSUN2 (Abbasi‐Moheb et al, 2012; Khan et al, 2012; Martinez et al, 2012); FTSJ1 (Dai et al, 2008; Freude et al, 2004; Froyen et al, 2007; Gong et al, 2008; Guy et al, 2015; Ramser et al, 2004; Takano et al, 2008); WDR4 (Chen et al, 2018; Shaheen et al, 2015; Trimouille et al, 2018); KEOPS complex (Braun et al, 2017); PUS3 (Abdelrahman, Al‐Shamsi, Ali, & Al‐Gazali, 2018; Shaheen, Han, et al, 2016); CTU2 (Shaheen, Al‐Salam, El‐Hattab, & Alkuraya, 2016; Shaheen, Mark, et al, 2019); TRMT10A (Gillis et al, 2014; Igoillo‐Esteve et al, 2013; Narayanan et al, 2015; Yew, McCreight, Colclough, Ellard, & Pearson, 2016; Zung et al, 2015); PUS7 (de Brouwer et al, 2018; Shaheen, Tasak, et al, 2019); and ALKBH8 (Monies, Vagbo, Al‐Owain, Alhomaidi, & Alkuraya, 2019).…”
mentioning
confidence: 99%